The Influence of Technology Performance Durability in the Cost-Optimal Analysis of a ZEB. (June 2019) - Danza, L; Bellazzi, A; Devitofrancesco, A; Guazzi, G
Abstract: The high number of existing buildings needing refurbishment actions justifies the need of a methodology that considers its service life after the refurbishment process. Cost-effectiveness assessment of refurbishment scenarios in building design is a crucial phase in the decision-making process towards a ZEB realization. Energy renovations involve an important investment, whose amount increases considerably when a ZEB target is fixed. When cost-optimal methodology is applied to different refurbishment scenarios, the costs evaluated take into consideration not only the initial investment cost, but also the running costs over the years and the payback time of the adopted solutions. Nevertheless, technologies hypothesized in the scenarios undergo a process of performance decay taking place since the first year of buildings' operations. The thin balance between needs and energy supply of a ZEB may be broken by deteriorating the energy performance of the whole building. Consequently, the running costs can increase significantly over the years and also the payback time, calculated over the annual costs of the building. The goal of this paper is to apply a cost-optimal assessment on a reference building, comparing the results of simulations with durability approach and those that do not consider the performance decay.